Efek Pemikatan (Attraction Effect) dan Bias Status Quo Sebuah Eksperimen dalam Perilaku Pengambilan Keputusan Portofolio Keuangan - bayu Laksma Pradana (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2021)
The reference dependent preference plays a significant role in individual choice behavior. Introducing a third option which is asymmetrical dominated to the dominating option can influence one’s decision. The status quo, endowment and attraction or decoy effect are the main noises. Such noises are proof to counter the rational choice theory. This paper tries to observe the status quo and decoy effect. Existence of those two effects are examined in experimental observation with 32 respondents. Questionnaires are set for respondents to dig information about how their answers contain choices. Two and three varies alternatives are presented to see respondent choice feedback when a third inferior alternative is available. The result shows respondent tendency to switch options when status quo becomes a reference point.